A probiotic modulates the microbiome and immunity in multiple sclerosis - Tankou, Stephanie K. (Ann Neurol, 2018)
OBJECTIVE: Effect of a probiotic on the gut microbiome and peripheral immune function in healthy controls and relapsing-remitting multiple sclerosis (RRMS) patients. METHODS: MS patients (N=9) and controls (N=13) were orally administered a probiotic containing Lactobacillus, Bifidobacterium and Streptococcus twice daily for two months. Blood and stool specimens were collected at baseline, after completion of the 2-month treatment, and 3 months after discontinuation of therapy. Frozen peripheral blood mononuclear cells (PBMCs) were used for immune cell profiling. Stool samples were used for 16S rRNA profiling and metabolomics. RESULTS: Probiotic administration increased the abundance of several taxa known to be depleted in MS such as Lactobacillus. We found that probiotic use decreased the abundance of taxa previously associated with dysbiosis in MS including Akkermansia and Blautia. Predictive metagenomic analysis revealed a decrease in the abundance of several KEGG (Kyoto Encyclopaedia of Genes and Genomes) pathways associated with altered gut microbiota function in MS patients such as methane metabolism following probiotic supplementation. At the immune level, probiotic administration induced an anti-inflammatory peripheral immune response characterized by decreased frequency of inflammatory monocytes, decreased mean fluorescence intensity (MFI) of CD80 on classical monocytes as well as decreased HLA-DR MFI on dendritic cells. Probiotic administration was also associated with decreased expression of MS risk allele HLA-DQA1 in controls. Probiotic induced increased in the abundance of Lactobacillus and Bifidobacterium were associated with decreased expression of MS risk allele HLA.DPB1 in controls. INTERPRETATION: Our results suggest that probiotic could have a synergistic effect with current MS therapies.